New pathological findings in emphysema of childhood: 3. Unilateral congenital emphysema with hypoplasia—and compensatory emphysema of contralateral lung. Issue 2 (March 1971) - Henderson, R.; Hislop, Alison; Reid, Lynne
Abstract : A quantitative study is here reported on the lungs of a child of 9 months with unilateral emphysema associated with hypoplasia, and with compensatory emphysema in the contralateral lung. The left lung was judged to show congenital hypoplasia because of the reduced number of bronchi and arteries, its small volume, and a total alveolar number less than that normally found at birth. This last was due mainly to reduction in the number of acini, the intra-acinar number seeming little affected. As the alveoli were eight times the normal volume, the case was considered to be one of congenital hypoplastic emphysema. The right lung was evidently normal at birth, since it had a normal number of bronchi, arteries, and alveoli. The lung was increased in volume due to an increase in alveolar volume—an example of compensatory emphysema. This case is discussed with relation to two previously reported cases of lobar emphysema and other cases in the literature. It is emphasized that a quantitative analysis of the state of bronchi, alveoli, and blood vessels is important to establish the nature of the pathological change. A preliminary classification based on the anatomical features is offered.